Integrated Care Using the ABCstroke Pathway Improves Cardiovascular Outcomes and Survival in Patients with First-Ever Ischaemic Stroke - Christopher T. W. Tsang; Sylvia E. Choi; Tommaso Bucci; Jia-Yi Huang; Qing-Wen Ren; Mei-Zhen Wu; Wen-Li Gu; Ran Guo; Jing-Nan Zhang; Anthony O. T. Ma; Steven H. M. Lam; Yap-Hang Chan; et al. (Global Heart)
Background: A recent position paper of the European Society of Cardiology Council on Stroke proposed an integrated ABCstroke pathway to optimise post-stroke management. We evaluated the impact of ABCstroke pathway adherence on post-stroke cardiovascular outcomes. Methods: Patients with first-ever ischaemic stroke in Hong Kong between 2006 and 2022 were included in this retrospective cohort study. Multivariable Cox regression analysis was performed to evaluate the association between physicians’ adherence to the ABCstroke pathway and the primary outcome, which was a composite of recurrent ischaemic stroke, transient ischaemic attack, haemorrhagic stroke, myocardial infarction, heart failure and all-cause mortality. Results: Of the 9,669 included patients with ischaemic stroke (mean age 69.6 ± 13.4 years; 57.5% male), 58.1% were optimally managed according to all three ABCstroke pillars. After 1 year of follow-up, adherence to the ABCstroke pathway was associated with a lower risk of the primary composite endpoint (hazard ratio (HR): 0.80; 95% confidence interval (CI): 0.72–0.88), as well as a lower risk of haemorrhagic stroke (subdistribution hazard ratio (SHR): 0.50; 95% CI: 0.38–0.67), heart failure (SHR: 0.771; 95% CI: 0.596–0.998), cardiovascular death (SHR: 0.64; 95% CI: 0.45–0.90), and all-cause mortality (HR: 0.72; 95% CI: 0.62–0.85). Risk reductions in the primary endpoint increased progressively with a higher number of ABCstroke criteria obtained. No significant interaction was observed in the association according to age, sex, or stroke severity. Conclusions: In this cohort of Asian patients with first-ever ischaemic stroke, optimal management according to the ABCstroke pathway was associated with a reduction in the risk of adverse outcomes.